Markers of Cirrhosis and Inflammation in HIV/HBV Co-infection in a Ugandan Cohort. (4th October 2017) - Copeland, Nathanial K; Eller, Michael A; Creegan, Matthew; Esber, Allahna; Crowell, Trevor A; Eller, Leigh Anne; Semwogerere, Michael; Kibuuka, Hannah; Kiweewa, Francis; Cham, Fatim; Ganesan, Kavitha; Polyak, Christina S; et al.
Abstract: Background: Co-infection with HIV and hepatitis B virus (HBV) is common, reaching 23% in Uganda, and can accelerate HBV disease progression. Inflammation contributes to the pathogenesis of both viruses. We compared serological biomarkers of inflammation and FIB-4 scores (to predict liver fibrosis) stratified by HIV and HBV status in a Ugandan cohort. Methods: Subjects with HIV/HBV co-infection were matched up to 2:1 by age and gender with HIV-monoinfected, HBV-monoinfected, and uninfected controls from the Ugandan site of the African Cohort Study (AFRICOS). Demographic and laboratory characteristics, including inflammatory biomarkers, were compared between the groups. FIB-4 scores were stratified as <1.45, 1.45–3.25, and >3.25 for those unlikely to have advanced fibrosis, indeterminate, and likely to have advanced fibrosis, respectively (resp.), in the HIV/HBV and HIV groups, which had these data available. Results: Within the Ugandan subset of AFRICOS, 31 HIV/HBV co-infected patients were available and compared with 62 HIV-monoinfected, 7 (all that were available) HBV-monoinfected, and 62 uninfected subjects. Median age was 37 (range 19–67) years and 78% were male. The HBV group, as compared with the HIV/HBV, HIV, and uninfected groups, had higher prevalence of hepatitis C antibody (29%, 6%, 2%, 3%, resp.; P = 0.04), fewer other active infections (0%, 48%, 52%, 26%, resp.; P = 0.002), fewer non-antiretroviral medications (median 0, 1, 2, 0, resp.; P < 0.001), and a smaller proportion on an antimicrobial (0%, 32%, 37%, 18%, resp.; P = 0.03). The HIV/HBV group had generally higher levels of inflammation overall and statistically had significantly higher levels of MMP-12 and lower levels of FGF-23 compared with the other groups (Figure 1). The HIV/HBV group had a lower proportion of subjects unlikely to have advanced fibrosis by FIB-4 (Figure 2; P = 0.046). Conclusion: Elevated MMP-12 in the HIV/HBV group suggests that elastin degradation may be a mechanism contributing to the accelerated progression of liver disease seen in co-infection. Prior literature demonstrated that FGF-23 is elevated in end-stage liver disease and predicts mortality, but we did not observe higher levels in HIV/HBV co-infection in this cohort with little advanced liver disease. Further studies are needed to characterize the inflammatory milieu and evaluate the impact of time and treatment of HIV/HBV. Disclosures: T. A. Crowell, Gilead Sciences: Speaker, Speaker honorarium